Predictors of Infarct Growth in Patients with Large Vessel Occlusion Treated with Endovascular Therapy - Simonsen, Claus Z.; Mikkelsen, Irene K.; Karabegovic, Sanja; Kristensen, Pia Kjaer; Yoo, Albert J.; Andersen, Grethe (Frontiers in Neurology, 2017)
Introduction: Endovascular therapy (EVT) is now evidence based in anterior circulation stroke caused by large vessel occlusion. Outcome is related to infarct size, but data on predictors of infarct growth is limited. We analyzed our cohort of EVT patients primarily selected by Magnetic Resonance Imaging (MRI) to examine predictors of infarct growth and the association between infarct size and outcome. Methods: We identified 342 patients with anterior circulation stroke from 2004 to 2014 in our prospectively collected EVT database. Baseline infarct size was available for 281 (measured by MRI) while final infarct size was available for 312 patients. Functional outcome was defined by modified Rankin Score (mRS) after 90 days and good outcome was defined as mRS 0-2. Predictors of infarct growth were examined by regression analysis. Results: Successful reperfusion (odds ratio (OR) 0.17, 95% Confidence Interval (CI) (0.09-0.33) was the strongest predictor of reduction of infarct growth. Receiving intraveneous thrombolysis and a short time span from symptom onset to scanning also reduced infarct growth. Occlusion of the internal carotid artery intracranially predicted infarct growth (OR =7.29, 95% CI: 2.36-22.53). EVT under general anesthesia and having a NIHSS between 10-15 were also associated with infarct growth. Discussion: Failure of reperfusion resulted in an average infarct growth of approximately 50 ml. Lack of reperfusion generally results in a poor outcome likely due to infarct growth. Occlusion of the intracranial internal carotid artery and EVT under general anesthesia predicted infarct growth, while successful reperfusion, getting intraveneous thrombolysis and a short time span from onset to scan protected against growth. A median infarct size of 52 ml best discriminates between a good and a bad outcome.